Ebt2 film dosimetry using imagej software analysis at high energy photon beams - Ramli, Nur Amirah Nabila (Universiti Sains Malaysia, 2016)
The aim of this study is to evaluate the dosimetry parameters using ImageJ software and conventional software, Verisoft software. The EBT2 film was irradiated with 400 MU for 6 MV and 10 MV energy photon of Siemens Primus (LINAC). The film was cut into 3x3 cm and exposed to 0 cGy - 600 cGy doses for calibration purposed. Another film from the same batch of EBT2 film was used to measure percentage depth dose (PDD) and beam profile.The film was scanned 24 hr after irradiation with Epson Expression 10000 XL flatbed scanner. The percentage depth dose (PDD) and beam profile were analyzed using Verisoft (5.1) and ImageJ softwares. The result showed that the calibration curve using ImageJ for 6 MV and 10 MV energy photon excellent linearity (R = 0. 982 and 0.981 respectively).The percentage discrepancy for PDD was calculated for each 1 cm depth. The small percentage discrepancy between ImageJ and Verisoft is 0.72 % and between ImageJ and ionization chamber is 0.23 % for 6 MV PDD. The percentage discrepancy of 10 MV between ImageJ and Verisoft is 0.41 % and between ionization chamber is 0.28 %. The flatness of beam profile by ImageJ is 3.2 % and Verisoft is 5.0 % for 6 MV energy photon the beam flatness of 10 MV energy photon for ImageJ is 4.27 % and Verisoft is 1.97 %. The penumbra at 6 MV energy for Verisoft is -5.5 and + 5 and for ImageJ is -4.5 and +4. At 10 MV for Verisoft, the penumbra is - 4 and +5 and for ImageJ - 4 and + 4.5. The symmetry at the 6 MV is 0.96 % for Verisoft and 1.6 % for ImageJ. The symmetry of the 10 MV for Verisoft and ImageJ is 0.17 % and 0.054 % respectively. As the conclusion the ImageJ can be used as the alternative film quality assurance software due to its good agreement with conventional software, Verisoft.